(3TQM eYdbI WQag Hf GdYHOs - (3WQag Hf GdYHO , WQaI Hf GdYHO Hf SajGf Hf SYO GdHcQj GdhGFdj, CHh YeQhs
(3ChdgG (B:s
(3fMhdg CWdGd HHQbI KgeO JdhM cHGbi GdhTe ai XGgQ GdjO s
(3BNQgG (B:s
(3CNj Kbg dG jfKfi Yf VQHjI EPG bjd egdkG , bGd MGLRg bO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3GdTGYQ gh WQaI Hf GdYHO Hf SajGf Hf SYjO GdHcQi GdhGFdi GdeJhai (B60(3g`s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B225s
Keywords: (3GdCOHs